Engineering a Macroscopic Adhesion System Inspired by Mucilaginous Seeds - Ufuk Gürer; Felicitas von Usslar; Cordt Zollfrank; Oliver Lieleg (Advanced Materials Interfaces, 2024)
Abstract Wet adhesion is a challenging process that requires successful interactions between the two surfaces of interest. Current adhesives may offer sufficient strength but often contain toxic components. Thus, when the field of adhesion meets bioinspiration, there is lots of potential for finding an innovative solution. Here, inspired by mucilaginous seeds and by using refined fiber structures provided by renewable materials, it is demonstrated how to build a comparably strong wet adhesive system. The process involves the controlled fibrillation of a wood surface followed by the application of a macromolecular coating employing the main component found in mucilaginous seeds. Moreover, the additional introduction of a thermo‐responsive polymer into the system allows for obtaining control over the strength and the compliance of the detachment process. Thus, this study demonstrates how combining renewable materials with a multi‐step coating process offers an environmentally friendly solution that pinpoints a promising path toward bio‐based wet adhesives.